2016
DOI: 10.1136/tsaco-2016-000041
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of femoral fractures care as a measure of trauma care between level I and level II trauma systems in Israel

Abstract: BackgroundOur hypothesis in this study was that the outcome of patients with femur fractures would be favorable in a level I trauma center (LITC).MethodsA prospective multicenter cohort study. 5 LITC and 6 regional (level II) trauma centers (RTCs) were enrolled to participate in the study. A total of 238 patients suffering from a femoral fracture were recruited to the study. 125 patients were treated in LITCs and 113 in RTCs. Data were extracted from the emergency medical services ambulances, emergency departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…After removing duplicates, 4,151 records were screened on title and abstract, resulting in 122 potentially eligible studies. After full-text screening 32 studies were included 21–52 . Three additional studies were identified using reference chasing, 53–55 resulting in 35 included studies for the systematic review; 10 studies on traumatic brain injuries (TBIs), 22,26,29,30,33,45,49,50,53,54 six studies on thoracic injuries, 21,25,27,28,46,55 six studies on abdominal injuries, 34,35,38,47,48,52 three studies on spinal cord injuries, 23,37,41 five studies on lower-extremity injuries, 24,39,40,42,43 and five studies on hemodynamically unstable patients 31,36,44,51,54 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing duplicates, 4,151 records were screened on title and abstract, resulting in 122 potentially eligible studies. After full-text screening 32 studies were included 21–52 . Three additional studies were identified using reference chasing, 53–55 resulting in 35 included studies for the systematic review; 10 studies on traumatic brain injuries (TBIs), 22,26,29,30,33,45,49,50,53,54 six studies on thoracic injuries, 21,25,27,28,46,55 six studies on abdominal injuries, 34,35,38,47,48,52 three studies on spinal cord injuries, 23,37,41 five studies on lower-extremity injuries, 24,39,40,42,43 and five studies on hemodynamically unstable patients 31,36,44,51,54 …”
Section: Resultsmentioning
confidence: 99%
“…Most (n = 32, 91%) studies were retrospective cohorts, 21–34,36,37,39,41–53,55 three (9%) studies were prospective cohorts 35,40,54 . The majority (n = 32, 91%) were United States based, 21–23,25–30,32–39,41–55 one study was conducted in France, 24 one in Israel, 40 and one study in Canada 31 . A total of 26 (74%) studies 22–27,29–32,34–36,38–40,43–52 compared Level I with Level II trauma centers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations